THE USE OF PROGRAM AND PEDAGOGICAL MEANS OF TEACHING IN THE PROCESS OF STUDYING MATHEMATICS AS THE WAY OF REALIZATION OF COMPETENT APPROACH - Bibik, Г. (Journal of Information Technologies in Education (ITE), 2010)
The possibility of usage of informational technologies of education while studying basic school mathematics is being viewed.